Physical-spatial Analysis of Sanandaj to Optimal Positioning of Physical Developmental of the City - Hossein Nazmfar; Anvar Amanallahpour; Ali Eshgi (جغرافیا و پایداری محیط)
The increasing growth of cities, affected by population growth and migration, leading to unplanned constructing and lots of changes in spatial structures, especially physical developmental of city in unfavorable natural areas. This fact makes it necessary to focus on urban issues, particularly its physical issues. Knowledge of the spatial form of the city can be a contributing factor in the success of urban planners and practitioners. The present study aims at analyzing and understanding the physical space of Sanandaj to provide a model of future development by fuzzy logic. The methodology is a descriptive- analytic one. Moreover, the raw data were collected through documentary and field studies. The models for urban form determining like Entropy and Holden were applied to analyze the data. Google Earth Arc GIS 10.2 software were used to represent the findings. The results indicate that, according to the calculation of Entropy coefficient, Sanandaj has dispersed and non-condensing pattern. Based on Holden model, it turns out that approximately 57% of the physical growth of the city is related to the growth of the population while 43 percent of urban growth is related to urban horizontal and spiral growth. The findings from analysis indicate that the spatial data show that natural factors make serious constrains inside or around the city, as only a small percentage of the total area is considered as appropriate cores for physical-spatial urban expansion.